A case series: cytomegalovirus retinitis following autologous hematopoietic cell transplantation: a call for early detection and aggressive management - Zhou, Yanhan; Liu, Mengyun; Zhang, Juntao; Lu, Ying; Ye, Peipei (Frontiers in Medicine, 2025)
BackgroundCytomegalovirus (CMV) retinitis represents a rare yet vision-threatening opportunistic infection following autologous hematopoietic cell transplantation (auto-HCT), typically arising in the setting of profound iatrogenic immunosuppression. While CMV reactivation is a well-documented post-transplant complication, the occurrence of retinitis remains uncommon, and its clinical course and risk profile in auto-HCT recipients are inadequately characterized. Our findings underscore a novel association with delayed immune reconstitution and propose a strategy for enhanced surveillance and preemptive intervention.Case presentationBetween November 2019 and January 2025, six patients who underwent auto-HCT for a range of hematologic malignancies were diagnosed with CMV retinitis. The median age at presentation was 63 years. All patients were seropositive for CMV-IgG prior to transplantation. The universal presenting symptom was visual impairment, manifesting as either decreased visual acuity or blurred vision. CMV DNAemia was detectable in four (66.7%) patients at diagnosis. Bilateral ocular involvement was noted in four (66.7%) cases. 66.67% patients had received high-dose corticosteroid therapy, and five (83.33%) had been treated with monoclonal antibodies prior to the onset of retinitis. A consistent immunological finding was persistent lymphopenia with markedly low CD4+ T-cell counts (median 167 cells/μL). Management primarily involved intravitreal ganciclovir injections in the majority of affected eyes. Three patients (Patients 1, 4, and 6) experienced improved visual outcomes, while the other three (Patients 2, 3, and 5) had worsened vision. The all-cause mortality rate was 83.3% (5/6 patients), with fatalities attributed to concurrent infections, hemorrhage, and underlying disease progression.ConclusionCMV retinitis is an emerging and serious complication after auto-HCT, strongly correlated with prolonged immunosuppression–particularly from T-cell-depleting monoclonal antibodies and corticosteroids–resulting in sustained CD4+ T lymphopenia. To enable early detection and intervention that may improve visual outcomes, we advocate for proactive ophthalmologic surveillance in patients–particularly those with high-risk persistent CMV DNAemia, severe lymphopenia, or any ocular symptoms (irrespective of systemic CMV DNAemia status). This surveillance should comprise extended immune monitoring and routine fundoscopic examinations to facilitate timely diagnosis.